2018
DOI: 10.1002/hpja.2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise at an onsite facility with or without direct exercise supervision improves health‐related physical fitness and exercise participation: An 8‐week randomised controlled trial with 15‐month follow‐up

Abstract: Providing a workplace exercise facility to complete an individually-prescribed 8-week exercise program is sufficient to improve health-related physical fitness in the short-term independent to the level of supervision provided, but does not influence long-term participation. SO WHAT?: Lower cost onsite exercise facility supervision is as effective at improving physical health and fitness as directly supervised exercise, however ongoing support may be required for sustained physical activity behaviour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The improvements reported herein were achieved with a total time commitment of < 50 min per week; one third of the current guidelines for moderate continuous exercise [ 48 ]. That the benefits achieved were largely indistinguishable between the two HIIT groups, contests the need for supervision to optimise the benefits of exercise [ 49 ], a notion supported by previous work reporting on middle-aged adults [ 50 ]. Although there appears to be no data reporting the impact of HIIT supervision in older adults, in young [ 34 ] and middle-aged [ 33 ] adults, and in adults with type 1 diabetes [ 51 ] and heightened cardiovascular disease risk [ 52 ], supervision was not shown to enhance adaptation.…”
Section: Discussionmentioning
confidence: 78%
“…The improvements reported herein were achieved with a total time commitment of < 50 min per week; one third of the current guidelines for moderate continuous exercise [ 48 ]. That the benefits achieved were largely indistinguishable between the two HIIT groups, contests the need for supervision to optimise the benefits of exercise [ 49 ], a notion supported by previous work reporting on middle-aged adults [ 50 ]. Although there appears to be no data reporting the impact of HIIT supervision in older adults, in young [ 34 ] and middle-aged [ 33 ] adults, and in adults with type 1 diabetes [ 51 ] and heightened cardiovascular disease risk [ 52 ], supervision was not shown to enhance adaptation.…”
Section: Discussionmentioning
confidence: 78%
“…Third, many job roles within universities involve prolonged sedentary behaviour throughout the working day (Alkhatib, 2013), creating a significant opportunity for change (Buckley et al , 2015). This final point may in part explain the recent finding that employees who enrolled into a university workplace exercise programme were mostly overweight with poor cardiorespiratory fitness (Hunter et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, most interventions were of short duration (5–12 weeks) without long-term follow-up, with low overall participation rates acknowledged as a limiting factor to the wider positive impact on employee health and fitness. Since this review, a university-based randomised controlled trial reported a significant decrease in weekly onsite exercise training session attendance by employees over eight weeks (from a mean 1.9 to 1.4 sessions per week), regardless of whether they received 1:1 exercise supervision in addition to onsite facility access or not (Hunter et al , 2018). Collectively, these data suggest that workplace exercise programmes are efficacious for improving health, fitness and exercise participation in the short-term, but these programmes require refinement to increase engagement and adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of respondents indicated that the level of physical activity prior to the current pandemic was moderate or high. Similarly, participants predominately reported that both their general and mental health were “good” or “very good.” The evidence base for the relationships between physical activity, including mind-body focused physical activity, 51 54 and physical health 51,54 58 and mental health 52 54,59 are well established. Additionally, there is evidence of a bidirectional association between mental health and physical activity, 60 62 suggesting that mental health status may influence the ability or decision to participate in physical activity.…”
Section: Discussionmentioning
confidence: 99%